Nudity, Protest and the Law in Uganda - Tamale, Sylvia (Strategy, Voice, Power, 2016)
The past few years in Uganda have witnessed several incidents of women stripping naked as a way of protesting what they perceive as gross injustice. This lecture attempts to analyze this age-old strategy from the perspectives of law, gender and power. In so doing, the institution of the law is understood broadly to include written legislation, unwritten customary law and the religious principles which underlie our legal jurisprudence. I step back in history to retrace naked protests in Africa before analyzing the local phenomenon. The analysis is guided by poststructural feminist understandings of the human body as a site of both power and control. This approach uses the imagery of bodies marked by written scripts which can be ―read‖ and interpreted by society. Of major concern to the analysis is the role played by the law in ―inscribing‖ the scripts of power and domination on men‘s bodies, while simultaneously inscribing subordination, passivity and sexuality on the bodies of women. I also examine how the law responds to naked protests. My conclusion is that, through the spectacle of naked protests, women are attempting to re-write the script on their bodies by using nakedness as an instrument of power and to subvert the law in order to effect justice.